Growth Inhibition of Botrytis cinerea Fungus on Strawberry (Fragaria sp.) Using Kaffir Lime (Citrus hystrix) Leaf Essential Oil Emulsion - Nofia, Nita; Martosudiro, Mintarto; Muhibuddin, Anton (Agro Bali : Agricultural Journal, 2024)
Post-harvest damage is caused by biological factors such as the attack of Botrytis cinerea pathogenic fungi. causes gray mold rot disease to be a source of problems in strawberry production. This study aims to determine the potential of kaffir lime leaf essential oil emulsion as an antifungal against Botrytis cinerea. The fungus was isolated from strawberry fruit samples that showed symptoms of gray mold disease. Fungal isolation was carried out through the direct planting method and antifungal inhibitory ability test by food poisoned method with potato extract agar media. This experiment used a completely randomized design consisting of 6 treatments with 5 repetitions. The results showed that kaffir lime leaf essential oil emulsion contains secondary metabolites that can inhibit 100% of the growth of Botrytis cinerea pathogenic fungal colonies. Essential oil concentrations of 0.10%, 0.15%, and 0.20% had a significant effect on the growth of Botrytis cinerea pathogenic fungi.